2015
DOI: 10.1007/s12350-014-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

Stress thallium-201/rest technetium-99m sequential dual-isotope high-speed myocardial perfusion imaging validation versus invasive coronary angiography

Abstract: Dual-isotope high-speed MPI is reliable at detecting or ruling out CAD. NCT01785589.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
(44 reference statements)
0
8
0
2
Order By: Relevance
“…Because of the geometry of detection and focused acquisition, the ratio between acquired 201 Tl myocardial counts and total acquired counts is better with CZT cameras, approximately 0.35 to 0.50 versus 0.15 to 0.20 with Anger cameras [31][32][33]. The published studies conclude that with CZT cameras and 201 Tl, acquisition times can be reduced down to 4-6 min or injected activities decreased down to 0.7 MBq/kg with high quality images [33].…”
Section: Dual Perfusion Imagingmentioning
confidence: 99%
“…Because of the geometry of detection and focused acquisition, the ratio between acquired 201 Tl myocardial counts and total acquired counts is better with CZT cameras, approximately 0.35 to 0.50 versus 0.15 to 0.20 with Anger cameras [31][32][33]. The published studies conclude that with CZT cameras and 201 Tl, acquisition times can be reduced down to 4-6 min or injected activities decreased down to 0.7 MBq/kg with high quality images [33].…”
Section: Dual Perfusion Imagingmentioning
confidence: 99%
“…2 Many of these studies have assessed the diagnostic performance of MPI with CZT cameras (Table 1). 1,[3][4][5][6][7][8] Further, in a meta-analysis by Nudi et al, the sensitivity of CZT SPECT was found to be range between 0.78 and 0.89 and the specificity ranged from 0.62 to 0.76. 9 While the sensitivity is comparable to prior studies, the specificity is lower.…”
Section: Czt Versus Conventional Spectmentioning
confidence: 95%
“…3 The authors propose a fast test, which was utilized in 1,336 patients, but analyzed in only 214 patients. Using the GE Discovery NM 530 high-efficiency SPECT camera (GE Healthcare), a mean dose of 82 MBq (2.2 mCi) of Tl-201 was injected at peak stress, 5 minutes stress imaging followed and a mean dose of 314 MBq (8.5 mCi) of Tc-99m was injected after stress imaging and 5 minutes rest imaging followed 2 minutes later.…”
Section: See Related Article Pp 513-522mentioning
confidence: 99%